Degradation of chicken feathers by Aphanoascus keratinophilus and Chrysosporium tropicum strains from pellets of predatory birds and its practical aspect. (July 2020) - Bohacz, Justyna; Korniłłowicz-Kowalska, Teresa; Kitowski, Ignacy; Ciesielska, Anita
Abstract: The present study is the first report on the biodegradation of native keratin by fungi isolated from food pellets of birds of prey. The aim of the study was to evaluate the diversity of keratinolytic activity of 2 fungal species, Aphanoascus keratinophilus and Chrysosporium tropicum, isolated from pellets of raptors and to find a relationship between the origin of fungal strains and their keratinolytic activity. The feather weight loss ranged from 60% to 75% for A. keratinophilus and from 55% to 70% for Ch. tropicum . Strains isolated from kestrel and buzzard pellets transformed feathers after 6 weeks into a soluble protein form in the range from 11% to 17% and 12%–17%, respectively. A. keratinophilus strains transformed feather N into N–NH4 + maximally in 53% and minimally in 20%, whereas Ch. tropicum strains converted from approx. 3%–42%. Feather S was transferred to the medium as S–SO4 2- after 42 days in 74% by A. keratinophilus and from 2% to 68% by Ch. tropicum strains. The effectiveness of fungal strains isolated from buzzard and kestrel pellets, was generally higher than that of strains isolated from owl pellets. The passage of the tested fungal strains through the gastric barrier and their thermo-tolerance allow a conclusion that pellet-derived keratinolytic fungi (especially from diurnal raptors) are a suitable inoculum material for keratin waste composting. Graphical abstract: Image 1 Highlights: Undigested food resources of birds-pellets-are a source of fungi. Fungi from pellets are active in biodegradation of chicken feathers. The tested A. keratinophilus and Ch. tropicum strains are thermo-tolerance. Feather weight loss after 8 weeks of culturing these fungi was 55–75%. The most effective strains were isolated from buzzard's and kestrel's pellets.